Pride and Prejudice - Austen, Jane, 1775-1817 (Lahore, Pakistan Readings, 2016)
In this classic 19th century story of love battling pride, we meet Elizabeth Bennet. Elizabeth is a smart, well-rounded woman, and she is one of five unmarried daughters of the country gentleman, Mr. Bennet. The Bennets' small town is in an uproar when two highborn, eligible gentlemen, Mr. Bingley and Mr. Darcy, come to stay. Elizabeth's prideful self does not realize her life is about to change when she meets the intolerable Mr. Darcy, who will make her question her sensibilities.
Keywords: England -- Courtship -- Young women